Paritas Dengan Kejadian Anemia Pada Ibu Hamil di Puskesmas Wringinanom Kabupaten Gresik - Dwi Ertiana; Dewi Taurisiawati Rahayu; Windhy Arfianti (STIKES dan AKZI Karya Husada Kediri, 2022)
Anemia is a problem that often occurs in pregnant mothers. Many factors influence the incidence of anemia in pregnant mothers, one of which is parity. Parity is of particular concern because it is one of the most dominating factors in the occurrence of anemia in pregnancy. The purpose of this research was to determine the correlation of parity with anemia incidence in pregnant mothers at wringinanom public health center gresik regency. The research design used correlational analysis using a cross-sectional approach. The sampling technique is Simple Random Sampling, obtained a sample of 86 respondents from a total population of 576 pregnant mothers, the study was conducted at the Wringinanom Health Center, Gresik Regency on 9-14 May 2022. The instrument used was an observation sheet of medical record data. Data analysis using the Spearman test. The results showed that more than half of 44 respondents (51.2%) had primiparous parity and less than half of 38 respondents (44.2%) were known to have no incidence of anemia. The results of the analysis showed that value = 0.000 < 0.05, which indicates that H1 is accepted, meaning that there is a correlation of parity with anemia incidence in pregnant mothers at wringinanom public health center gresik regency with a strong correlation level of (r) 0.740. Anemia in pregnancy can be influenced by many factors, one of which is parity. Parity is one of the factors that dominate the occurrence of anemia in pregnancy because the mother's condition is too frequent to experience pregnancy and childbirth causing iron not to be formed optimally. So the parity of the respondents has an impact on the incidence of anemia in pregnancy. Pregnant mothers should increase their iron intake and regularly consume Fe tablets.